A perspective of nanotechnology in hypersensitivity reactions including drug allergy - Montañez-Vega, María Isabel; Ruiz-Sánchez, Antonio Jesús; Perez-Inestrosa, Ezequiel (Lippincott Williams & Wilkins, 2010)
Purpose of review We provide an overview of the application of the concepts of nanoscience and nanotechnology as a novel scientific approach to the area of nanomedicine related to the domain of the immune system. Particular emphasis will be paid to studies on drug allergy reactions. Recent findings Several well defined chemical structures arranged in the dimension of the nanoscale are currently being studied for biomedical purposes. By interacting with the immune system, some of these show promising applications as vaccines, diagnostic tools and activators/effectors of the immune response. Even a brief listing of some key applications of nanostructured materials shows how broad and intense this area of nanomedicine is. Summary As a result of the development of nanoscience and nanotechnology applied to medicine, new approaches can be envisioned for problems related to the modulation of the immune response, as well as in immunodiagnosis, and to design new tools to solve related medical challenges. Nanoparticles offer unique advantages with which to exploit new properties and for materials to play a major role in new diagnostic techniques and therapies. Fullerene-C60 and multivalent functionalized gold nanoparticles of various sizes have led to new tools and opened up new ways to study and interact with the immune system. Some of the most versatile nanostructures are dendrimers. In their interaction with the immune system they can naturally occurring macromolecules, taking advantage of the fact that dendrimers can be synthesized into nanosized structures. Their multivalence can be successfully exploited in vaccines and diagnostic tests for allergic reactions.
Keywords: Alergia a los medicamentos; Allergy drug reactions